Synthesis of Methyl Ester Nitrate from Mahogany Seed Oil (Swietenia mahagoni Linn) - Musta, Rustam; Nurliana, Laily; Halulanga, Muh. Mahatir (Indonesian Journal of Chemical Research, 2021)
Nitration of methyl ester from mahogany oil (Swietenia mahagoniLinn) can be produced by Methyl Ester Nitrate (MEN), an additive that is useful for increasing Cetane Numbers in diesel fuel. This study aims to determine the yield of MEN that can be produced from mahogany seed oil after esterification, trans-esterification, and nitration and to identify the MEN compounds produced. Mahogany oil is obtained by pressing mahogany seeds and then degumming to remove the gum. Mahogany oil-free gum is esterified using methanol with the mole ratio of oil: methanol (1: 6), then trans-esterified, also using methanol with mole ratio (1:15) and a methyl ester is obtained. Then the methyl ester was nitrated with HNO3, sulfuric acid, and acetic anhydride to obtain a translucent reddish colored MEN product with a yield of 24.99%. The success of the synthesis was shown by the FTIR spectrophotometer in the presence of absorption at 1550 cm-1 which indicated the presence of the C-ONO2 group, the absorption at 1365 cm-1 indicated the presence of the NO2 group, and at 1118 cm-1 indicated the presence of the C-N group. The reaction mechanism that occurs during the predicted nitration reaction is an electrophilic substitution reaction and nucleophilic addition.